Level of integration in current undergraduate curricula of two private-sector medical colleges in Karachi - Naila Baig; Faiza Siddiqui; Mirza Altamish Muhammad Baig; Iram Khursheed; Khubaib Muhammad Shamim Meah (Canadian Medical Education Journal, 2022)
Background: Diverse strategies are employed globally to integrate medical curricula. Nevertheless, a gap exists in assessing the role of medical instructors in meaningful integration. We developed and used a tool to explore the current level of integration, score medical instructors’ individual practices for integration, and investigate contextual elements minimizing integration.